In-service English teachers' beliefs of grammar teaching and classroom practices at primary schools in Selangor, Malaysia / Azrina Abu Bakar - Abu Bakar, Azrina (2013)
The study of English teachers’ beliefs about grammar teaching and the influence of such beliefs on their actual classroom practices have been subjected to many discussions and empirical research in second language education. This paper reports on a study which investigated the beliefs of in-service English teachers about grammar teaching and actual classroom practices at primary schools in Selangor, Malaysia. Questionnaires were distributed to 50 English teachers to determine teacher’s beliefs towards grammar teaching and to investigate their teaching procedures in the English classroom. Furthermore, four teachers were interviewed and observed; the interviews explored the teachers’ beliefs of grammar teaching and classroom practices, while the non-participatory observations provided insights into how they teach grammar in the classrooms and examine whether the teachers’ beliefs about grammar teaching are aligned with their actual classroom practices. Findings revealed the Malaysia primary schools in Selangor English teachers do have a set of beliefs about grammar teaching and generally those participants’ beliefs about grammar teaching were matched with their actual classroom practices. However, the findings also found a small number of discrepancies observed from some participants mostly due to pupils’ level of English proficiency and contextual constraints such as time constraints. There are three implications of the research are also discussed in this study.